Adult Educators and Asthma Health Educators in Community Settings: Buddies or Foes? - Augustine M. Amenyah (Adult Education Research Conference, 2013)
Asthma prevalence continues to increase across the United States of America, affecting 24.6 million people and projected to affect over 40 million people by 2025 ( Healthy People, 2010). Healthcare use for asthma is high and disparities remain in asthma healthcareuse and reimbursement. The most recommended asthma management is control of symptoms and prevention of adverse outcomes NHLBI, 2003, EPR-3, 2007; AAPCEH, 2003).